Early detection and population dynamics of Listeria monocytogenes in naturally contaminated drains from a meat processing plant - Annette Fagerlund; Trond Møretrø; Merete Rusås Jensen; Solveig Langsrud; Birgitte Moen (Frontiers in Microbiology)
Listeria monocytogenes, a significant foodborne pathogen, often contaminates ready-to-eat foods through cross-contamination in food processing environments, and floor drains represent one of the most common sites of persistence. Subtyping of L. monocytogenes from food processing plants for the purpose of source tracking is usually performed on a single colony obtained after selective enrichment. This study investigates the temporal variation and population dynamics of L. monocytogenes in drains, focusing on the diversity of L. monocytogenes and the impact of the resident microbiota. Six different drains in a meat processing plant were each sampled four times over a period of 8 weeks and subjected to two-step selective enrichment in Half Fraser and Full Fraser broths. The clonal complexes (CCs) of at least 20 individual L. monocytogenes isolates from each positive sample (460 isolates in total) were determined using either the GenoListeria Multiplex qPCR assay or whole genome sequencing (WGS). The microbiota in drains and enrichment cultures was analyzed by 16S rRNA gene amplicon sequencing and metagenomic or quasimetagenomic sequencing. L. monocytogenes was detected in the majority of samples and four different CCs were identified – CC9, CC11 (ST451), CC121 and CC8 – with up to three CCs in the same sample and with different CCs dominating in different drains. The same clones of CC9, CC11, and CC121 had persisted in the facility for 3–5 years. The composition of the drain microbiota remained relatively stable over time, with Pseudomonas, Acinetobacter, Janthinobacterium, Chryseobacterium, Staphylococcus, and Sphingomonas as the most commonly identified genera. There were no apparent differences in the microbial genera present in L. monocytogenes positive and negative drains or samples. The study highlights the use of techniques such as qPCR and quasimetagenomics for monitoring and controlling the risk of L. monocytogenes contamination in processing environments.